2015
DOI: 10.3341/kjo.2015.29.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, a Biochemical Tool for Differentiating Ischemic and Nonischemic Central Retinal Vein Occlusion during the Early Acute Phase

Abstract: PurposeThe purpose of the study was to differentiate ischemic central retinal vein occlusion (CRVO) from nonischemic CRVO during the early acute phase using plasma homocysteine as a biochemical marker.MethodsFasting plasma homocysteine, serum vitamin B12, and folate levels were measured in 108 consecutive unilateral elderly adult (age >50 years) ischemic CRVO patients in the absence of local and systemic disease and compared with a total of 144 age and sex matched nonischemic CRVO patients and 120 age and sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A study by Lahiri et al compared the levels of plasma homocysteine in adult age ≥ 50 years old affected with iCRVO (n=108) (defined by Hayreh's morphological criteria described in section II. Definitions, above), with non-iCRVO (n=144) and age and sex matched healthy controls (166) . Homocysteine level was significantly increased in patients with iCRVO when compared with that in non-iCRVO patients and control subjects (166) .…”
Section: A Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Lahiri et al compared the levels of plasma homocysteine in adult age ≥ 50 years old affected with iCRVO (n=108) (defined by Hayreh's morphological criteria described in section II. Definitions, above), with non-iCRVO (n=144) and age and sex matched healthy controls (166) . Homocysteine level was significantly increased in patients with iCRVO when compared with that in non-iCRVO patients and control subjects (166) .…”
Section: A Etiologymentioning
confidence: 99%
“…Definitions, above), with non-iCRVO (n=144) and age and sex matched healthy controls (166) . Homocysteine level was significantly increased in patients with iCRVO when compared with that in non-iCRVO patients and control subjects (166) . Other reported potential associations include deficiencies of the coagulation inhibitor proteins C and S and antithrombin III, whereas the role of reduced levels of Factor XII remains controversial with some studies suggesting an association while others do not (8,23,160,278) .…”
Section: A Etiologymentioning
confidence: 99%
“…After screening of all titles and abstracts of potentially relevant articles, a total of 10 studies met the inclusion criteria ( Fig. 1 ) 11 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , while three studies were excluded from the meta-analysis for reporting reasons, since they did not include mean ± SD values 26 , 27 , 28 . The study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…An interesting study was presented by Francesco Sofia et al, who demonstrated on 262 patients with RVO that low levels of vitamin B6 and folic acid, and elevated levels of homocysteine are independently associated with an increased risk of retinal vein occlusion, while the level of vitamin B12 is not statistically significant [96]. Despite the findings of Cahill and Sofi's research, other studies have indicated a connection between low levels of vitamin B12 and the occurrence of retinal vein occlusion [97,98].…”
Section: Homocysteine B Vitamins and Folic Acidmentioning
confidence: 97%